(untitled) (The Geographic Base, 2019)
Climate change is one of the crucial and inevitable issues in the earth though people can minimize on contribution and can adapt coping strategies. Although, Nepal contributes very less part of the total in the factors of climate change, local people are observing significant changes which leading many challenges. As a result, the livelihood of local people is being more critical. Based on the data collected from the 7 wards of Mangaltar VDC in Khotang district, the result shows the changing pattern indicators of climate change and its impact on crops production. In addition, the findings illustrate the local adaptation strategies on changing environment in the period of last thirty years.